Ecovillage scale-up and its well-being challenges: a case study from Norway - Amsale K. Temesgen (Sustainability: Science, Practice, & Policy)
Ecovillages are settlements that aim to combine human well-being and environmental sustainability. They serve as sites of social learning for sustainable consumption practices and may inspire lifestyle changes in mainstream society. However, most ecovillages fail in the first few years of establishment. Through an in-depth study of a Norwegian ecovillage’s efforts at expansion, this article explores the factors that adversely affected the well-being of ecovillage residents and threatened the community’s survival. The study applies mixed methods combining needs-based workshops, a well-being survey, and in-depth interviews. The transformation of the ecovillage into a larger settlement with modern houses was driven by a developer and with minimal involvement of residents. The resulting divergence in visions and values, coupled with structural problems of the homes, led to protracted conflicts, and resulted in the developer’s bankruptcy. The study identifies strong social institutions and affordable infrastructures as crucial elements for both well-being and the success of ecovillages.